Contract cheating and blackmail: A risky business? - Yorke, Jon; Sefcik, Lesley; Veeran-Colton, Terisha (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2020)
This study examines the emergent issue of blackmail and contract cheating through a scenario-based online exercise completed by 587 university students in Western Australia. Participants were presented with two consecutive scenarios, each involving a difficult assignment. The possibility of blackmail was introduced prior to (and within) the second scenario. The exercise included survey questions which examined participants’ knowledge and attitudinal perspectives towards the issue of contract cheating and blackmail. Although a small percentage of students (2.4%) elected to cheat in this study, almost 90% claimed not to have been aware of the risk of blackmail. Knowledge of the risk of blackmail reduced the number of students willing to cheat by half. Some participants had direct or indirect experience of blackmail, revealing new insights into the providers of cheating services. Possible approaches to the issue of blackmail are examined in the light of the implications of this research.